Expression and steroid hormone regulation of TETs and DNMTs in human endometrium. Issue 2 (August 2020) - Mahajan, Vishakha; Osavlyuk, Diana; Logan, Philip C; Amirapu, Satya; Ponnampalam, Anna P
Abstract : DNA methyltransferases (DNMTs) and ten-eleven translocation proteins (TETs) facilitate methylation and hydroxymethylation of DNA, respectively. DNMTs are widely studied with conflicting results on their regulation in the endometrium. While the role of TETs in the endometrium remains relatively unexplored. Deregulated expression of TETs and DNMTs are associated with endometrial pathologies. The aim of this study is to characterize the temporal TET expression in endometrium and to determine the hormonal regulation of TETs in comparison to DNMTs . mRNA expressions were quantified by real-time PCR in endometrial tissues from cycling women and localization was determined by immunohistochemistry. Hormonal regulation was investigated in endometrial epithelial and stromal cell lines following a 24 and 48 h treatment cycle. TET1 and 3 mRNA expressions were significantly upregulated in the mid-secretory phase. TET protein expression was ubiquitous in endometrial epithelium throughout the menstrual cycle except during the late-secretory phase, while stromal staining was scattered. TET1 mRNA was significantly upregulated in response to estrogen in stromal cells. Transcriptions of all three TETs were induced in response to progesterone treatment in epithelial cells. Only DNMT3b in epithelial cells and DNMT1 in stromal cells were significantly upregulated upon 24-h estrogen exposure following a significant decrease of DNMT1 when treated with 24 h of estrogen and progesterone. This study suggests that TETs are expressed in a cell-specific, dynamic manner in the endometrium and are responsive to steroid hormones. Investigating the role of TETs individually and with respect to DNMTs, will help to elucidate gene regulatory mechanisms in endometrial biology and pathologies.